Effectiveness of therapeutic programs for students with ADHD with executive function deficits - Napalai Chaimaha (2018)
© 2017 Taylor & Francis. The purpose of this study was to investigate the effectiveness of therapeutic programs, an executive function training program and a collaborative program, for students with attention-deficit/hyperactivity disorder (ADHD) with executive function deficits (EFDs), especially regarding working memory, planning, and monitoring. The participants were eight students diagnosed with ADHD with EFDs between 10–12 years old and “supporters” (parents, teachers, principals, and peers). The eight students participated in EF trainings three times weekly for seven weeks. A one-group pretest–posttest design measured changes in executive functions (EFs) using the Tower of London-Drexel University (TOLDX), Wechsler Intelligence Scale for Children-Revised (WISC-R; Digit Span subtest), and the Behavior Rating Inventory of Executive Function (BRIEF) pre- and postintervention. The collaborative program taught “supporters” ways to assist students with ADHD with EFDs in improving their EFs. Statistically significant improvements (p <.05) with the Wilcoxon signed rank test were found for working memory, planning, and self-monitoring on the BRIEF (Teacher Form), and working memory in WISC-R. No significant differences within the group for the TOLDXwere found. School performance (as indicated by Grade Point Average) showed significant improvement. These findings indicate that these therapeutic programs were effective in improving EF for students with ADHD with EFDs.